(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2022)
This study aimed to find out the effectiveness of cognitive therapy based on full awareness in treating panic disorder that falls within the group of anxiety disorders, according to the Fifth Diagnostic and Statistical Manual of Mental Disorders (DSM5). A treatment program prepared by the researcher was applied, including cognitive reconstruction techniques in cognitive therapy on the one hand and La Pleine conscience technique used by Segal (2006) on the other hand. The study also used the two Beck 21 depression measures and the modified mental health scale by R SCL-90- by Derogatis & al, (1981) to measure changes in patients. The program was applied to a sample of patients visiting the Psychological Division at Al-Mouwasat Hospital in Damascus. The case of one of the patients reviewed by the division was selected to conduct a clinical study, according to the qualitative approach, and to document what has been applied to the patients Results showed the effectiveness of mindfulness-based cognitive therapy in treating panic disorder. As the symptoms of the disorder receded, the number of the patient’s panic attacks decreased, and the patient returned to her daily academic and social life after she had retired.